2006
DOI: 10.1016/j.bandl.2005.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of linguistic prosody: Evidence from syntactic disambiguation in the productions of brain-damaged patients

Abstract: The present investigation focussed on the neural substrates underlying linguistic distinctions that are signalled by prosodic cues. A production experiment was conducted to examine the ability of left-(LHD) and right-(RHD) hemisphere damaged patients and normal controls to use temporal and fundamental frequency cues to disambiguate sentences which include one or more Intonational Phrase level (IPh) prosodic boundaries.Acoustic analyses of subjects' productions of three sentence-types -parentheticals, appositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 58 publications
(71 reference statements)
4
18
0
3
Order By: Relevance
“…Although sample sizes for the brain-damaged participant groups were small, this finding is consistent with previous production studies investigating the use of prosodic cues to distinguish ambiguities at the sentence level (linguistic versus emotional prosody, or syntactic ambiguities), where results have Production of Prosodic Cues in Idioms 11 shown that both left-and right-hemisphere-damaged participants had fairly normal control over their production of prosodic cues Baum, Pell, Leonard & Gordon, 2001;Shah et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although sample sizes for the brain-damaged participant groups were small, this finding is consistent with previous production studies investigating the use of prosodic cues to distinguish ambiguities at the sentence level (linguistic versus emotional prosody, or syntactic ambiguities), where results have Production of Prosodic Cues in Idioms 11 shown that both left-and right-hemisphere-damaged participants had fairly normal control over their production of prosodic cues Baum, Pell, Leonard & Gordon, 2001;Shah et al, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…Finally, Gandour and colleagues (2003) suggest that the LH and RH preferentially process acoustic prosodic parameters over linguistic units of variable lengths, rather than absolute time windows. Thus, the short prosodic domain (LH) may span over a syllable or a word, and the long domain (RH) may span across a phrase or sentence (Gandour et al, 2003;Baum & Dwivedi, 2003;Shah, Baum & Dwivedi, 2006).…”
mentioning
confidence: 99%
“…No differences emerged regarding F 0 measures between groups. Shah, Baum, and Dwivedi (2006) reported similar findings in a study in which they asked LHD and RHD speakers to produce sentences with parenthetical, appositive, and tag syntactic constructions. Listeners had greater difficulty identifying productions of both RHD and LHD groups than the control group.…”
Section: Introductionsupporting
confidence: 67%
“…2001;Schirmer et al, 2001;Shah et al, 2006). An additional timing deficit that was observed in our LHD subjects was the insertion of pauses at non-syntactic junctures in compound noun constructions.…”
Section: Discussionmentioning
confidence: 97%
“…El hallazgo de una disociación doble entre la capacidad de repetir prosodia emocional y lingüística apoya el supuesto de independencia funcional entre la repetición de ambas clases de prosodia ya que la alteración de un tipo de ellas no implica necesariamente la alteración en la otra y viceversa. En trabajos anteriores se reportó que los pacientes con lesiones de HD pueden presentar alteraciones tanto para producir prosodia emocional (Cohen et al, 1994;Guranski & Podemski, 2015;Heilman et al, 2004;Wright et al, 2016) como lingüística (Ross, Shayya, & Rousseau, 2013;Shah, Baum, & Dwivedi, 2006). Por su parte, los resultados del presente trabajo permiten establecer, además, que esas alteraciones pueden mostrar una doble disociación que aportan evidencia a favor del postulado de independencia funcional entre ambos tipos de prosodia a nivel de la capacidad de producción.…”
Section: Discussionunclassified